Self-regulated digital citizen: A survey of Malaysian undergraduates - Nordin, Mohamad Sahari (American-Eurasian Network for Scientific Information Publisher, 2015)
The purpose of the study was to examine the degree to which students’ self-regulated behaviors influence their ethical behaviors and self-protecting use of digital technology. Data were collected from 250 undergraduates who were studying at 10 higher learning institutions in Malaysia, using a 9-item digital citizenship questionnaire. To address the research objectives, the data were subjected to confirmatory factor analysis and structural equation modeling. The results of data analysis supported the research hypotheses, in which students’ digital citizenship is a valid and reliable multidimensional construct, and students’ self-regulated behavior influences their ethical and self-protecting digital behaviors. The findings suggest for further research and instructional interventions, in particular in the curriculum implementation, which need to be aligned to students’ development of self-regulatory capabilities